TECHNICAL STUDY OF SPUN PILE CONSTRUCTION SLAB ON PILE KATARAJA TOLL ROAD PROJECT ZONE 1 - Arrizal Ilham Muttaqin; Gotot Slamet Mulyono (Jurnal Ekonomi, 2023)
Slab on pile is one of the bridge structures consisting of slab, pile head, and spun pile used in the Kataraja Toll Road Project zone 1. The piles on the slab on pile bridge on the Kataraja Toll Road Project are five in one pile head which has a spacing of 1 meters. Piling in slab on pile construction with pile foundations with a diameter of 60 cm. During the piling process, some data is generated, including the number of strokes and the final set of calendering results. In this paper the analysis of the bearing capacity of the piles will use several methods, namely the Meyerhof 1976 method which is a static method using SPT data then for data from calendering results it is used in the dynamic method, namely Modified ENR, Danish formula, Janbu's formula, and Michigan State Highway formula Commission. There is also a PDA test and Allpile Program, which is one of the technical tests for the feasibility of the pile, where this test aims to determine the axial bearing capacity of the pile, the integrity of the pile and the energy efficiency transferred. The data from the results of the PDA test will later be used to check or validate the bearing capacity of the piles. The technical study of slab on pile construction with spun pile foundations in zone 1 of the Kamal – Teluk Naga – Rajeg (Kataraja) toll road aims to ensure that the pile foundations can be said to be safe and efficient in terms of spun pile depth and spun pile bearing capacity.